A long‐acting pegylated recombinant human growth hormone (Jintrolong®) in healthy adult subjects: Two single‐dose trials evaluating safety, tolerability and pharmacokinetics. (29th June 2018) - Guan, Y.; He, F.; Wu, J.; Zhao, L.; Wang, X.; Huang, L.; Zeng, G.; Ren, B.; Chen, J.; Liao, X.; Ma, Z.; Chen, X.; et al.
Summary: What is known and objective: Jintrolong ® is a pegylated recombinant human growth hormone (rhGH) (PEG‐rhGH) developed for weekly subcutaneous (sc) injection. The current human tolerability trial and pharmacokinetics (PK) trial evaluated the safety, tolerability and PK of single‐dose Jintrolong ® injection in healthy adult subjects. Methods: Both trials were single‐centre, randomized, open‐label and single‐dose studies. In the human tolerability trial, 34 healthy subjects were randomized to receive single‐dose Jintrolong ® sc injection (0.01, 0.06, 0.2, 0.5 or 0.8 mg/kg) or placebo. In the PK study, 30 healthy male subjects were evenly randomized into 3 groups to receive single‐dose Jintrolong ® sc injection (0.1, 0.2 or 0.4 mg/kg), and the subjects receiving 0.4 mg/kg Jintrolong ® were given a single sc injection of conventional rhGH (0.067 mg/kg) after a 14‐day washout period. Safety and PK profiles of Jintrolong ® were evaluated. Results and discussion: Jintrolong ® was well tolerated with no serious adverse events or local injection responses. The PK trial showed that the plasma growth hormone concentration elevated quickly and stayed at peak level between 12 and 48 hours post‐Jintrolong ® injection, then decreased gradually back to baseline within 168 hours. Compared to single‐dose conventional rhGH, Jintrolong ® at all doses demonstrated significantly longer half time and time to maximum plasma concentration, lower clearance and higher systemic drug exposure, indicating prolonged presence of GH in the subjects' circulation. Additionally, systemic exposure to Jintrolong ® increased in a dose‐dependent manner. What is new and conclusion: Single‐dose Jintrolong ® injection was well tolerated in healthy adult subjects, and the maximum tolerable dose was no lower than 0.8 mg/kg. Jintrolong ® was long‐acting with the potential for weekly administration. Abstract : Mean plasma GH concentrations (± SEM) (ng/ml) vs. time profile of subjects receiving single dose of 0.1, 0.2, or 0.4 mg/kg Jintrolong ® (PEG‐rhGH) and of subjects in the Jintrolong ® 0.4 mg/kg group receiving a subsequent single dose of 0.067 mg/kg conventional rhGH after a 14‐day wash‐out period.